Induction of gonadal maturation at different temperatures in burbot Lota lota. Issue 5 (20th September 2016) - Schaefer, F. J.; Hermelink, B.; Husmann, P.; Meeus, W.; Adriaen, J.; Wuertz, S.
Abstract : A rearing experiment was conducted to test whether temperature protocols that differed from a simulation of natural conditions might induce maturation after isothermal grow‐out in burbot Lota lota . Lota lota were acclimated to two different temperature regimes: low temperature (LT), close to natural temperature at 4·0° C and elevated, high temperature (HT) at 8·5° C over 40 and 27 days respectively, with all fish then wintered for 47 days. Every second fish was treated with a gonadotropin‐releasing hormone analogue. Maturational competence of oocytes was assessed with a germinal vesicle breakdown assay using a novel staining strategy. In both treatments, puberty and maturational progress occurred, characterised by an elevated gonado‐somatic index and advanced gonadal stages (histological analysis). Progress of gonadal maturation was reflected by elevated plasma concentrations of testosterone and 11‐ketosterone in males and 17β‐oestradiol in females. Ovulation was not observed. Sperm could be activated equally across treatments. In general, LT was more effective than HT treatment, indicated by advanced gonadal stages, higher numbers of oocytes undergoing germinal vesicle breakdown in vitro and elevated sex steroid levels. Hormone treatment could improve effectiveness at HT. In conclusion, less drastic temperature regimes as previously reported in combination with hormone treatments seem sufficient to induce maturation in L. lota after isothermal grow‐out.